Histological study of the effect of Pegenumharmalaseed extract on liver, liver enzymes andsome blood parameters in male Albino Rats - Adeeb Mahdi, Lina; Hannon Hashim, Jasem (Al-Qadisiyah Journal of Pure Science, 2018)
Present study was carried out to find the effect of Pegenumharmala on liver tissue, liver function test and some blood parameters on experimental animals, thus for this purpose ,Four groups of male albino rats (Musmusculus) were subcutaneously administrated with normal saline(0.9 % NaCl) or Peganumharmala aqueous seed extract (1%,2%,3%) mg/ kg)/body weight at daily interval for one month period. Thereafter, animals were scarified and specimens from the liver were examined under light microscope for structural changes. Repeatedtreatment withPeganumharmala seeds aqueous extract caused dose- related structural changes in the liver treated groups. Severe changes were observed following 2 % mg/ kg dose that were manifested by fibrosis in interstitial connective tissueand blood vessels of the liver. repeated treatment of Peganumharmalwater extract a seeds at 3% mg/ kg dose caused severe destruction of hepatic cellnucleiand vesiculation in the cytoplasm due to degeneration in hepatic cells .In addition, dis arrangement in hepatic sinusoids and destruction in the walls of central veins wereobserved. Nuclear polymorph cellular infiltration and cirrhosis as wellas pyknotic in hepatic cell nuclei were noticed in the 1% mg/ kg dose group. Peganumharmalaseedsaqueous extract at 1% and 2% mg/ kg caused slight to moderatehistological changes in the liver manifested as degeneration and hypertrophy of tubular epithelial lining. In addition,The oral administration of extractcauses maximum fall of blood glucose level to(138 and 35.5 ) at(p<0.01) respectively with the normal ratsCholesterol was decreasedsignificantly ( 0.01 ) in treatedgroup compared with control . Lowestvalue was in second dose 2% (29.0) while the highest value was in control group (148.5),significant changes (0.05) in GPT and GOT enzymes were observedbetween treated and control group. The highest values were incontrol groups while the lowest values were in treated groupNon-significant changes were observed in the values of WBC and RBC intreated rats compared to controls. In conclusions Peganumharmala seed extract has many histopathological effect on liver tissue as well as moderate effects on liver enzymes and some blood parameters.